The Influence of Real-Time Feedback on Excavator Operator Actions in Footing Excavation: Machine Guidance and Conventional Methods - Hyunsik Kim; Jeonghwan Kim; Bangyul An; Taeseok Song; Jaehoon Oh; Minki Kim; Seungju Lee (Applied Sciences)
Excavator operations play a critical role in the productivity of earthworks, yet traditional methods often rely heavily on operators’ intuition and experience, which can lead to inconsistent outcomes. This study investigates how machine guidance (MG) providing real-time feedback relating to excavation depth and slope can modify operators’ actions and improve performance compared with conventional excavation methods. A controlled experiment was conducted at an active construction site, in which four footings were excavated using the two approaches under similar conditions. The results demonstrated that MG excavation reduced the total duration of the work from 3650 s to 2652 s and decreased the number of excavation cycles from 68 to 57, underscoring the impact of timely, precise guidance on efficiency. Moreover, the average fill factor improved from 3.04 under conventional methods to 3.47 with MG, suggesting more consistent and optimal loading of the bucket. These findings confirm that real-time feedback can enhance operator confidence, reduce unnecessary movements, and foster systematic excavation strategies. This study thus provides empirical evidence that MG can significantly optimize excavation performance, highlighting the need for broader adoption of this technology in modern construction practices.